Therapeutic Applications of Extracellular Vesicles for Myocardial Repair - Liu, Chunping; Bayado, Nathan; He, Dongyue; Li, Jie; Chen, Huiqi; Li, Longmei; Li, Jinhua; Long, Xinyao; Du, Tingting; Tang, Jing; Dang, Yue; Fan, Zhijin; et al. (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular disease is the leading cause of human death worldwide. Drug thrombolysis, percutaneous coronary intervention, coronary artery bypass grafting and other methods are used to restore blood perfusion for coronary artery stenosis and blockage. The treatments listed prolong lifespan, however, rate of mortality ultimately remains the same. This is due to the irreversible damage sustained by myocardium, in which millions of heart cells are lost during myocardial infarction. The lack of pragmatic methods of myocardial restoration remains the greatest challenge for effective treatment. Developing methods of repair and regeneration of damaged myocardium is a major goal of cardiovascular research. Exosomes are small extracellular vesicles actively secreted by all cell types that act as effective transmitters of biological signals which contribute to both reparative and pathological processes within the heart. Exosomes have become the focus of many researchers as a novel drug delivery system due to the advantages of low toxicity, little immunogenicity and good permeability. In this review, we discuss the progress and challenges of extracellular vesicles in myocardial repair, and review the recent development of extracellular vesicle-loading systems based on their unique nanostructures and physiological functions, as well as the application of engineering modifications in the diagnosis and treatment of myocardial repair.